Decentralization in Argentina - Nadir Habibi; Cindy Huang; Diego Miranda; Victoria Murillo; Gustav Ranis; Mainak Sarkar; Frances Stewart (Yale University, Economic Growth Center, 2001)
Human development, reflected in the status of people's levels of health and education, affects future growth and, in turn, is affected by decentralization. Unlike earlier exclusive emphasis on budgetary issues, this study focuses on the impact of fiscal decentralization on the level of human development. It traces the origin and recent development of revenue-sharing arrangements across Argentina's provinces over time (1970-94). The study regresses two indicators of health and educational status on two decentralization measures. It highlights the link between decentralization and human development outcomes and suggests that devolutionary decentralization has a positive influence on the effectiveness of public policy directed towards an improvement in the level of human development. Decentralization is shown to reduce intra- regional disparities and increase levels of human development. While the paper also recognizes problems associated with decentralization, including addressing inter-regional disparities, the positive impact of decentralization schemes on human development is seen to be of relevance in evaluating the Argentine co-participation regime which is currently under negotiation.
Keywords: O18; 330; Fiscal Decentralization; Human Development; Argentina; Finanzbeziehungen; Dezentralisierung; Gesundheit; Bildung; Argentinien